The Green Deal and The Common Agricultural Policy in The Context Of Post-Pandemic and Current Geopolitical Challenges - Olimpia Smaranda MINTAŞ; Cristina Maria MAERESCU; Irina-Adriana CHIURCIU; Aurelia Ioana CHEREJI; Daniela ȚUȚUI; Ioan CHEREJI (Communications of International Proceedings, 2022)
This paper addresses a topic of general interest - namely the relationship between the Green Deal and the Common Agricultural Policy (CAP) in the context of post-pandemic and current geopolitical challenges. Since its inception, the Green Deal has never been designed to meet such challenges, and therefore a number of adjustments are needed if the European Commission (EC) is to implement it successfully and with little opposition. An important aspect of the research was the attention paid to the case of Romania and the way in which the problems mentioned above impacted the local landscape and also what are the solutions considered at national level, taking into account the particularities of our country. The research was mainly desk research, which focused on the analysis of official European Union (EU) documents and their interpretation for Romania. The research goal is thus to present the current post-pandemic and geopolitical challenges that often are neglected when we speak about the Green Deal and the Common Agricultural Policy. They have an important political component that needs to be taken into consideration when analysing the decision-making process and the impact of their implementation. The main conclusions are that the current transitional measures for the Green Deal should be adapted in order to be successfully implemented and the paper tried to provide a number of scenarios and practical examples.
Keywords: CAP; current geopolitical challenges; Green Deal; post-pandemic; transition